Serum Expression of β-Catenin Is a Potential Detection Marker in Patients with Colorectal Cancer. (24th October 2019) - Li, Shue; Huang, Mao; Liu, Qiao; Wang, Ding; Wu, Rui; Zhang, Xiuyu; Chen, Weixian; Duan, Liang
Abstract : Object . To investigate the correlation between the level of serum β -catenin and the disease progression of colorectal polyp (CRP) and colorectal cancer (CRC) and find its potential diagnostic value. Methods . A total of 327 clinical serum samples and their electronic medical records were collected. Detecting by enzyme-linked immunosorbent assay (ELISA), the correlations of serum β -catenin with tumor marker carcinoembryonic antigen (CEA) and CRC clinicopathological parameters and the receiver operating characteristic (ROC) curve were analyzed. Results . Serum β -catenin levels in the CRP and CRC patients were significantly higher than those in the healthy control (HC) group (P < 0.05 and P < 0.001 ). Compared with CRP, serum β -catenin level in CRC was also increased (P < 0.05 ). However, there was no significant difference in gender, age, location, tumor size, Dukes staging, or metastasis (P > 0.05 ) between serum β -catenin and clinical parameters of CRC. There was no correlation between serum β -catenin levels and CEA in CRC patients (P = 0.14 ). ROC curve analysis showed that serum β -catenin possessed the maximum diagnostic efficiency in CRP (AUC = 0.73, P < 0.05 ) with 86.41% sensitivity and 51.56% specificity. β -Catenin combined with CEA had the highest diagnostic efficiency (AUC = 0.88, P < 0.05 ) with 81.88% sensitivity and 73.44% specificity. With CRC patients from CRP patients, ROC analysis of the combining detection (AUC = 0.70, P < 0.05 ) had the 70% sensitivity and 84.5% specificity. Conclusion . The serum β -catenin levels are gradually increased in CRP and CRC, while there is no correlation between its levels and CRC disease process. Single serum β -catenin or combined CEA would be one of the potential candidate biomarkers for colorectal disease diagnosis.